Screening pediatric testicular cancer: A literature review - Rafael Newlands Fontoura; Natalia Bonfim dos Santos; Marcio Sidney Di Blasi Franchini; Fernanda Ferreira Lima; Arovel Oliveira Moura Junior; Rafael Texeira Boden; Ricardo Vianna de Carvalho (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Introduction: Childhood cancer is the leading cause of death in patients aged 5-19 years. Testicular tumors (TT) comprise 1 to 2% of all pediatric solid tumors. Although rare, TTs are often misdiagnosed. Screening improves clinical practice and decision-making for early diagnosis.  Objective: To analyze the screening methods for detection of pediatric testicular cancer and contribute to the management of suspected cases. Methods: We conducted an integrative systematic review of the PubMed, EMBASE, and LILACS databases limited to records published between January/2013 and August/2018.  Results: Sixty articles were initially selected based on the presence of specific search terms on the article body, title, and abstract. Of those, nineteen articles were selected for a full review. Clinical signs were not evident in most studies, but 12 (63%) reported the presence of scrotal masses. Cryptorchidism, family history, and the presence of contralateral TT were identified as risk factors. Alpha-fetoprotein (AFP) was elevated in 73% of studies, but normal levels do not rule out a suspected diagnosis. Scrotal ultrasound (US) was instrumental in 73% of studies and Doppler US (32%) was able to detect nearly 100% of cases at diagnosis. Computed tomography (abdomen/chest) was required in 12 studies (63%) for confirmation of metastasis of testicular germ cell tumors. In 73% of studies, stages were subdivided based on the levels of serum tumor markers and the presence of metastasis. The inguinal-scrotal approach is suggested as the preferred method as it does not affect prognosis or require adjuvant therapy. There are minimum requirements for therapeutic retroperitoneal lymphadenectomy. In 14 studies (73%), advanced stages showed a good prognosis with surgery in combination with chemotherapy. TT histology and treatment are different for prepubertal and postpubertal patients. In the same 14 studies (73%), relapsed patients received chemotherapy. In eight studies (42%) the overall survival increased by five years and, in three of them, it increased 2 by 100% post-combination therapy.  Conclusion: Few studies have evaluated the prognosis, disease recurrence, and survival rates of children with testicular cancer. AFP, US and an appropriate surgical approach provide optimal personalized treatment and minimize the adverse effects.